Studies on factors affecting business performance of biotechnology companies [electronic resource) - Hesham Ali Metwally Ali El-Enshasy, 1968- (2012)
Thesis (Sarjana Pengurusan (Teknologi)) - UniversitiTeknologi Malaysia, 2012